Earnings management and sale of assets / Nor'azam Mastuki and Nihlah Abdullah - Mastuki, Nor'azam; Abdullah, Nihlah (Institute of Research, Development and Commercialization (IRDC), 2006)
The focus of this study is to examine whether firms used income from sale of assets as an instrument to manage earnings. Two aspect of earnings management are examined: earnings smoothing behavior and avoidance of debt covenant activities. A Sample had been taken from firms listed under industrial and consumer product at the main board of Bursa Malaysia from 2000 to 2003. Similar with findings obtained in an environment where current cost are applied in asset reporting, we found that incentive for earnings management is asymmetric.firms with poor economic performances (negative earnings change) have greater incentive to smooth earnings that firm exhibiting good economic performance (positive earning change). This study had also examined whether the asymmetric results holds true for firms selling asset with high impact on net income in comparison with firms selling asset with low impact on net income. an area which had not been explored by previous studies. And within this context we also found asymmetric results. Firms reporting high impact of income from asset sale in relation to net income had shown significant evidence ofearnings smoothing patterns. No evidence is found to associate earnings smoothing activities with firms reporting low impact of income from asset sale in relation to net income. However this research had failed to find evidence to associate income from asset sale with debt-equity hypothesis in all sub samples.